Dendritic Multipods: Sphere‐to‐Multipod Transmorphic Change of Nanoconfined Pt Electrocatalyst during Oxygen Reduction Reaction (Small 2/2019). Issue 2 (11th January 2019) - Yang, Juchan; Kang, Dongwoo; Jeon, Yuju; Lee, Jong Hoon; Jeong, Hu Young; Shin, Hyeon Suk; Song, Hyun‐Kon
Abstract : Durability of catalysts for the oxygen reduction reaction (ORR) should be guaranteed for long‐term operation of fuel cells. In article number1802228, Hu Young Jeong, Hyeon Suk Shin, Hyun‐Kon Song, and co‐workers design a catalyst/support system to confine platinum nanoparticles within holes of graphene for suppressing platinum agglomeration. Spherical multifaceted platinum particles are evolved to 110‐dominant dendritic multipods within the nano‐dimensional space during repeated ORR processes.